Thoughts on policy evaluations and technical constraints on vaccination (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The article analyses the relationship between the political judgements of the authorities responsible for regulating vaccination and the constraints imposed by 'science' and the technical data available to the decision-maker, also in the light of the way in which this relationship is treated by constitutional jurisprudence. A particular approach is adopted that takes the legislator's freedom of choice as its point of observation and examines the limits of admissibility that technical-scientific and judicial interventions that claim to bind legislative choices in these matters must encounter, precisely in the light of this freedom of choice.
Keywords: Vaccination; COVID-19; political discretion; scientific reasonableness; vaccine mandate